2011
DOI: 10.21825/scad.v2i1.20431
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of friction and wear: an overview

Abstract: In this age of virtual design, high-performance machines, and precise motion control, the abilityto characterize friction and wear processes and then to model and simulate them, becomes a pertinentissue. This communication gives a condensed overview of the generic characteristics of friction, thereafter,generic models, developed at KULeuven, PMA, are presented and discussed.with Leuven Air Bearings N.V. since Sept. 2010In regard to friction, both sliding and rolling are considered. The characterization concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Gambar 1. Kondisi permukaan kontak [13] Keausan adalah proses berkelanjutan dimana material terdegradasi setiap siklus. Banyak cara yang dilakukan untuk mengukur wear resistance dan wear rate seperti wear measuring equpments, mathematical modeling, tribo-meters dan simulations.…”
Section: Gesekanunclassified
“…Gambar 1. Kondisi permukaan kontak [13] Keausan adalah proses berkelanjutan dimana material terdegradasi setiap siklus. Banyak cara yang dilakukan untuk mengukur wear resistance dan wear rate seperti wear measuring equpments, mathematical modeling, tribo-meters dan simulations.…”
Section: Gesekanunclassified
“…Friction hysteresis not only occurs in lubricated contacts but can also be experimentally observed in dry contacts [18], and it is argued by Al-Bender [19] that within dry contacts, friction hysteresis originates from a time dependency in the local adhesion coefficient between interacting asperities. Thus far, several studies have revealed the existence of friction hysteresis and have provided some correlation between friction hysteresis and system properties (e.g., load, velocity, viscosity, and inertia); however, (i) the influence of system parameters on friction hysteresis and (ii) the influence of roughness and surface texturing are still open questions.…”
Section: Introductionmentioning
confidence: 97%
“…Another friction property is the hysteresis behavior presented by friction force as a function of displacement when the system start from zero velocity. The particular type of hysteresis exhibited by this presliding friction is rate-independent (Al-Bender and De Moerlooze, 2011). Additionally, it has non-local memory behavior, where the output at any time instant depends not only on any past value and the input history since then, but also on the past extremum values (Lampaert, 2003).…”
Section: Introductionmentioning
confidence: 99%